Burst-Like Transcription of Mutant and Wildtype MYH7-Alleles as Possible Origin of Cell-to-Cell Contractile Imbalance in Hypertrophic Cardiomyopathy - Montag, Judith; Kowalski, Kathrin; Makul, Mirza; Ernstberger, Pia; Radocaj, Ante; Beck, Julia; Becker, Edgar; Tripathi, Snigdha; Keyser, Britta; Mühlfeld, Christian; Wissel, Kirsten; Pich, Andreas; et al. (Frontiers in Physiology, 2018)
Hypertrophic Cardiomyopathy (HCM) has been related to many different mutations in more than 20 different, mostly sarcomeric proteins. While development of the HCM-phenotype is thought to be triggered by the different mutations, a common mechanism remains elusive. Studying missense-mutations in the ventricular beta-myosin heavy chain (β-MyHC, MYH7) we hypothesized that significant contractile heterogeneity exists among individual cardiomyocytes of HCM-patients that results from cell-to-cell variation in relative expression of mutated vs. wildtype β-MyHC. To test this hypothesis, we measured force-calcium-relationships of cardiomyocytes isolated from myocardium of heterozygous HCM-patients with either β-MyHC-mutation Arg723Gly or Arg200Val, and from healthy controls. From the myocardial samples of the HCM-patients we also obtained cryo-sections, and laser-microdissected single cardiomyocytes for quantification of mutated vs. wildtype MYH7-mRNA using a single-cell restriction digest approach. We characterized gene transcription by visualizing active transcription sites by fluorescence in situ hybridization of intronic and exonic sequences of MYH7-pre-mRNA. For both mutations, cardiomyocytes showed large cell-to-cell variation in Ca++-sensitivity. Interestingly, some cardiomyocytes were essentially indistinguishable from controls what might indicate that they had no mutant β-MyHC while others had highly reduced Ca++-sensitivity suggesting substantial fractions of mutant β-MyHC. Single-cell MYH7-mRNA-quantification in cardiomyocytes of the same patients revealed high cell-to-cell variability of mutated vs. wildtype mRNA, ranging from essentially pure mutant to essentially pure wildtype MYH7-mRNA. We found 27% of nuclei without active transcription sites which is inconsistent with continuous gene transcription but suggests burst-like transcription of MYH7. Model simulations indicated that burst-like, stochastic on/off-switching of MYH7 transcription, which is independent for mutant and wildtype alleles, could generate the observed cell-to-cell variation in the fraction of mutant vs. wildtype MYH7-mRNA, a similar variation in β-MyHC-protein, and highly heterogeneous Ca++-sensitivity of individual cardiomyocytes. In the long run, such contractile imbalance in the myocardium may well induce progressive structural distortions like cellular and myofibrillar disarray and interstitial fibrosis, as they are typically observed in HCM.